IMPACT OF THE COVID-19 PANDEMIC ON WORLD OCEAN POLLUTION - Zemlyanska, Olena; Polukarov, Yury; Polukarov, Oleksiy; Prakhovnik, Nataliia; Kovtun, Andrii; Snisarenko, Maria; Reznyk, Danylo; Martyniuk, Yelyzaveta (Collection of scientific papers «ΛΌГOΣ», 2024)
In 2010, the amount of plastic emissions was approximately 4.8-12.7 million tons, in 2015 this amount increased significantly. For example, the plastic waste of the USA has increased by 5 times, China by 8.1. Only about 9-12% of this plastic is recycled, the other 90% end up in rivers and oceans. Every year, the problem of plastic pollution increasingly affects the lives of people, as well as animals and plants. The world community is trying to reduce the production of plastic products or propose ways to eliminate plastic pollution, but so far there are no significant results, because the number of tons of plastic in the ocean is only increasing. Many factors affect this. In 2020-2021, one of these factors was the Covid-19 pandemic.